Rancang Bangun Alat Penyaring Udara dengan Ultraviolet Germicidal Irradiation (UVGI) Berbasis Protokol MQTT dan Android - Musyuniarsih, Sherly Saprilita; Lindawati, Lindawati; Sarjana, Sarjana (Patria Artha Technological Journal, 2022)
Clean and fresh air is essential for the survival of every living creature. However, getting some fresh air is very difficult. Some of the factors that cause difficulty in obtaining healthy and fresh air are due to increasing air pollution. Therefore, a system is needed that can maintain air levels in the room. So that the air in the room can circulate well and people can breathe healthy air for better survival. When the humidity of the room is above the normal limit, the mist maker will light up, so that the humidity of the room is maintained. The UV-C light will turn on and off automatically. The lights are on for 30 minutes, this is because the use of UV-C lamps for too long is not good.